Conductive 2D Conjugated Metal–Organic Framework Thin Films: Synthesis and Functions for (Opto‐)electronics. Issue 5 (23rd February 2022) - Liu, Jinxin; Chen, Yunxu; Feng, Xinliang; Dong, Renhao
Abstract : Two‐dimensional conjugated metal–organic frameworks (2D c‐MOFs), possessing extended π – d conjugated planar structure, are emerging as a unique class of electronic materials due to their intrinsic electrical conductivities. Taking advantage of the large‐area flat surface, 2D c‐MOF thin films allow facile device integration with sufficient electrode contact, high device stability, and high charge transport, thereby emerging as appealing active layers for a broad range of electronic applications. Synthesis and device investigation of thin films are of great importance for their further development, which are systematically summarized in the current review. Here, the authors firstly introduce the molecular structures of representative 2D c‐MOFs and present the fundamental understanding on structure–property relationships. After that, the state‐of‐art synthetic methodologies toward high‐quality 2D c‐MOF thin films are summarized, including exfoliation and reassembly (ERA), liquid‐interface‐assisted synthesis (LIAS), and chemical vapor deposition (CVD). By considering the advantages of 2D c‐MOF films in device integration, remarkable progress in (opto‐)electronic device applications are discussed, such as field‐effect transistors (FETs), chemiresistive sensors, photodetectors, superconductors, and thermoelectrics. In the end, the remained challenges about the development of 2D c‐MOF films for (opto‐)electronics are highlighted and possible future directions are proposed to address these challenges. Abstract : Recent advances on two‐dimensional conductive metal–organic framework (2D c‐MOF) thin films are comprehensively reviewed. 2D c‐MOF thin films with high electrical conductivities and unique physical properties appear as emerging electronic materials for diverse electronic applications. Reliable chemical synthesis methodologies and remarkable progress in various (opto‐)electronic applications of 2D c‐MOFs thin films are discussed.